Importance of and Satisfaction with Psychosocial Support among Cancer Patients and Survivors in Puerto Rico: Gender, Health Status, and Quality of Life Associations - Castro, Eida M.; Asencio, Gloria; Quinn, Gwendolyn P.; Brandon, Thomas; Gwede, Clement K.; Vadaparampil, Susan; Simmons, Vani; McIntyre, Jessica; Jiménez, Julio (Puerto Rico Health Sciences Journal, 2017)
Objective: To assess needs perceptions regarding the importance of and satisfaction with psychosocial support among cancer patients and survivors in Puerto Rico. Methods: A cross-sectional study was conducted in 181 participants (70 men and 111 women) who were either undergoing cancer treatment (patients) or had completed cancer treatment (survivors). Participants completed a sociodemographic and clinical characteristics questionnaire, and the Psychosocial Needs Inventory (PNI). Results: The participants reported having or having had prostate (36%) or breast (32%) cancer or some other cancer type (32%). Of the 149 participants reporting cancer type, 130 were classified as having a high perceived level of health and quality of life, and 19 were classified as having a low perceived level of health and quality of life. In terms of perceived needs, the highest level of importance were assigned to the Support Network (e.g. family, friends, neighbors, care professionals; M = 2.88, SD = 0.43) and Health Professional (e.g., patient–health professional relationship, etc.; M = 2.80, SD = 0.50) categories, and the Emotional and Spiritual category was given the lowest importance (e.g., help managing negative emotions and spiritual counseling, etc.; M = 2.62, SD = 0.66). These perceptions varied by gender, perceived health status, and date of diagnosis. Women assigned more importance to the Health Professional and Information categories. Conclusions: The results reflect the importance of considering psychosocial needs when providing psychosocial support to cancer patients and survivors. These findings are anticipated to inform services provided by psychosocial oncology support programs in Puerto Rico.